Is resection for noncolorectal, nonneuroendocrine liver metastases justified?. Issue 4 (11th January 2021) - Patkar, Shraddha; Niyogi, Devayani; Parray, Amir; Goel, Mahesh
Abstract: Introduction: The role of hepatectomy in non‐colorectal, nonneuroendocrine liver metastasis (NCNN) is not clearly defined. This study represents a step towards surgical frame‐shift as an integral part of treatment pathway in these heterogeneous, arbitrarily treated tumors. It aims to provide answers regarding favorable tumor types and patient profiles for which liver metastasectomy would prove beneficial. Materials and Methods: Retrospective analysis of prospectively maintained database of hepatectomy in NCNN liver metastasis. Results: A total of 50 patients out of 516 patients underwent liver resection during this period. In 27 patients, the liver metastases presented synchronously whereas the other 23 were metachronous. Median disease‐free interval (DFI) was 36 months. Gastrointestinal stromal tumors (GIST) were the most common type of primary malignancy (15, 30%). In 41 patients, the liver was the only site of metastases. At a median follow‐up of 32.5 months, 24 patients developed recurrences. Five‐year overall (OS) and disease‐free survival (DFS) for the entire cohort was 60% and 32%, respectively. Median OS was highest in the breast (93 months) followed by GIST (56 months). Patients with longer DFI showed improved OS. ( p  = .04). Conclusion: Liver resection for NCNN metastases is safe and feasible in selected patients with good survival outcomes. Longer DFI correlates with better survival.